EFFECT OF SOIL STIFFNESS AND GROUND DISPLACEMENT IN EARTHQUAKE RESPONSE OF BRIDGES WITH PILE FOUNDATION - R. Mahmudur; K. Izuka; K. Imamura; K. Koga; T. Ohtsuka; G. Aramaki (International Association of Lowland Technology, 2001)
Dynamic analysis was carried for earthquake response of prototype bridge structure with pile foundation in clay soil with sand base. Analysis was carried out for different soil stiffness parameter, Vs (shear wave velocity)- value using